Sumber Media Pembelajaran SD/MI - Sakinah, Nur Imanis (Maliki Interdisciplinary Journal, 2025)
Examining the important role of validation of learning media in elementary education, especially at the elementary school/Islamic elementary school level with the advancement of technology and various forms of media available, validation becomes essential to ensure that the media used is effective in achieving learning objectives. The validation process includes systematic steps, from goal setting to evaluation and implementation. This study also identified advantages, such as increased educational efficiency and student engagement, as well as disadvantages related to time and resources. The results of the validation of learning media can have a positive impact on students' understanding and motivation to learn. These findings emphasize that validation of learning media should be an integral part of the development and use of media in education to improve the overall quality of learning.